The Geoecological Evaluation of the Heritage Interest of Polygonal Soils Inherited in Alpine Mountains. The Example of the Col du Noyer (Massif du Dévoluy, Hautes Alpes, France) - Pierre Pech; Mahé Ajinca; Sylvain Abdulhak; Eric Hustache; Laurent Simon; Brigitte Talon (Revue de Géographie Alpine)
At an altitude of 1664 m, the Col du Noyer in the French Dévoluy Mountains, which is accessible in summer by road, is one of the most popular Alpine passes. It was located in an unglaciated area during the last Quaternary ice age and suffered the effects of the severe frost. Polygonal grounds formations have recently been discovered. Our study presents the results of the identification and characterisation of these formations as well as the floristic assemblages that currently occupy them. The analyses, carried out by a multidisciplinary team, consist of photo-interpretation, geomorphological, sedimentological and pedoanthracological studies. They confirm the presence of these inherited polygonal grounds. Floristic surveys reveal that these inherited periglacial formations constitute original habitats, favouring a strong local heterogeneity. The whole constitutes a natural complex requiring protection. Enhancing the heritage value of this site would constitute a means of protecting this complex, which is a rare geomorphological landscape in the Alps: educational both in terms of its understanding and its paleoenvironmental interpretation.